2018
DOI: 10.3389/fnint.2018.00020
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Medial-Prefrontal Cortex Impairs Interval Timing Precision, but Not Timing Accuracy or Scalar Timing in a Peak-Interval Procedure in Rats

Abstract: Motor sequence learning, planning and execution of goal-directed behaviors, and decision making rely on accurate time estimation and production of durations in the seconds-to-minutes range. The pathways involved in planning and execution of goal-directed behaviors include cortico-striato-thalamo-cortical circuitry modulated by dopaminergic inputs. A critical feature of interval timing is its scalar property, by which the precision of timing is proportional to the timed duration. We examined the role of medial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 62 publications
(103 reference statements)
4
22
5
Order By: Relevance
“…This constitutes an important test since scalar variability (proportionality of timing imprecision to target intervals) is a psychophysical signature of interval timing in healthy samples (Buhusi & Meck, ). Given that it allows for within‐group comparisons, the use of a dual‐peak procedure (Buhusi, Reyes, Gathers, Oprisan, & Buhusi, ) in future studies would be the ideal procedure to investigate this specific question.…”
Section: Discussionmentioning
confidence: 99%
“…This constitutes an important test since scalar variability (proportionality of timing imprecision to target intervals) is a psychophysical signature of interval timing in healthy samples (Buhusi & Meck, ). Given that it allows for within‐group comparisons, the use of a dual‐peak procedure (Buhusi, Reyes, Gathers, Oprisan, & Buhusi, ) in future studies would be the ideal procedure to investigate this specific question.…”
Section: Discussionmentioning
confidence: 99%
“…Smith and collaborators also showed that the mPFC disengages from the task during habit formation 35 . However, these results are at odds with several results showing the critical role of the mPFC in timing 15,23,24,36 . Particularly, results from different tasks show that this region's inactivation impaired the timing precision but not accuracy 23,24 .…”
Section: Discussionmentioning
confidence: 57%
“…Reports of the spiking activity of neurons involved in keeping track of time implicate regions like medial prefrontal cortex 5,8,[13][14][15] , motor cortex 10,16,17 , striatum 2,5,8,10,[18][19][20] , hippocampus 6,7 , thalamus 21 , substantia nigra pars compacta 22 , among others. Active manipulations of the physiological activity have also helped assess the involvement of these areas in timing, particularly in the medial prefrontal cortex 5,[22][23][24] and striatum 20 . However, because timing tasks usually require many training sessions, the neurophysiological process underlying their acquisition has been less studied.…”
Section: Introductionmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) studies indicate greater activation in the DLPFC in healthy participants during timing tasks (Rao et al, 2001; Hinton and Meck, 2004; Üstün et al, 2017). Additionally, the PFC is implicated in TP in animals, both in lesion studies (Buhusi et al, 2018), pharmacological studies (Matthews et al, 2012), and in animal models of SZ (Buhusi et al, 2013).…”
Section: Dorsal-lateral Prefrontal Cortex (Dlpfc) and Working Memory mentioning
confidence: 99%